Tidal energy assessment with hydrodynamic modelling - Imran, Ali; Andrew Ragai, Henry Rigit; Omar, Yaakob; Jane, Labadin; Altaf Hussain, Rajpar (The Indonesian Journal of Electrical Engineering and Computer Science (IJEECS), 2023)
The increasing demand for sustainable energy generation brings a need for tidal current energy resource exploration around the globe. Hydrodynamic modelling is an essential aspect to explore macro tidal sites. In the current research paper, a 2D hydrodynamic model is set up by utilizing the numerical application of Delft3D. The model is validated against the database results and the two macro tidal sites are identified along the coastline of Sarawak, Malaysia. The maximum available kinetic energy flux at the identified location is 0.6 kW/m2, during peak neap tide hours. This stands as a sound justification to have a detailed tidal energy assessment study in this area in future research.